Quantitative FRET Microscopy Reveals a Crucial Role of Cytoskeleton in Promoting PI(4,5)P2 Confinement - Maria J. Sarmento (MDPI AG, 2021)
Phosphatidylinositol 4,5-bisphosphate (PI(4,5)P2) is an essential plasma membrane component involved in several cellular functions, including membrane trafficking and cytoskeleton organization. This function multiplicity is partially achieved through a dynamic spatiotemporal organization of PI(4,5)P2 within the membrane. Here, we use a Förster resonance energy transfer (FRET) approach to quantitatively assess the extent of PI(4,5)P2 confinement within the plasma membrane. This methodology relies on the rigorous evaluation of the dependence of absolute FRET efficiencies between pleckstrin homology domains (PHPLCδ) fused with fluorescent proteins and their average fluorescence intensity at the membrane. PI(4,5)P2 is found to be significantly compartmentalized at the plasma membrane of HeLa cells, and these clusters are not cholesterol-dependent, suggesting that membrane rafts are not involved in the formation of these nanodomains. On the other hand, upon inhibition of actin polymerization, compartmentalization of PI(4,5)P2 is almost entirely eliminated, showing that the cytoskeleton network is the critical component responsible for the formation of nanoscale PI(4,5)P2 domains in HeLa cells.